Effects of Cognitive Behavior Therapy on Heart Rate Variability among Medical Students at a Teaching Institution in Jaipur, India - Neha Saboo; Sudhanshu Kacker; Jitender Sorout (APIK Journal of Internal Medicine)
Introduction: Heart rate variability (HRV) is the variation in the time interval between heartbeats. It is controlled by the autonomic nervous system, which also regulates many other vital body functions. HRV has been used as a noninvasive marker of cardiac autonomic activity and cardiovascular risk stratification. The present study aimed to investigate the effect of cognitive behavior therapy (CBT) on different domains of HRV and their correlation at baseline and after 3 months of intervention. Methods: After obtaining institutional ethical clearance, the study was conducted from July to October 2022 among 140 1st-year Bachelor of Medicine and Bachelor of Surgery students at a medical college in Jaipur, Rajasthan, India. Linear component, i.e., time and frequency domain, and nonlinear components, i.e., Poincare plot of HRV assessed at baseline and after the 3 months of CBT. Results: Findings show that there was a significant decrease in linear components, i.e., time domain and frequency domain parameters (P < 0.001) and nonlinear components Poincare plot standard deviation (SD) 1/SD2 (P < .0.001) after 3 months of CBT. Linear and nonlinear components of HRV were positively correlated (P < 0.01). Conclusion: The study indicates that after 3 months of CBT, the autonomic nervous system shifted toward parasympathetic dominance, which was assessed by linear components, time domain and frequency domain parameters, and nonlinear components, i.e., Poincare plot (SD1/SD2) of HRV.